Efeitos da terapia hormonal combinada de estrogênio e drospirenona sobre a reatividade coronariana em ratas ovariectomizadas espontaneamente hipertensas - Borgo, Mariana Veronez (2015)
Drospirenone (DRSP) is a progestin with antihypertensive properties. However, its effects on endothelium-dependent coronary vasodilation have not been evaluated. This study investigated the effects of combined therapy with E2 and DRSP on the endothelium-dependent vasodilation of the coronary bed of ovariectomized spontaneously hypertensive rats. Animals were randomly divided into Sham operated (Sham), ovariectomized (OVX), ovariectomized treated with E2 (E2) and ovariectomized treated with E2 and DRSP (DRSP) groups. Hemodynamic parameters were evaluated directly by cannulation of the femoral artery. Endothelium-dependent vasodilation in response to bradykinin in the coronary arterial bed was assessed using isolated hearts according to modified Langendorff method. Coronary protein expression of endothelial nitric oxide synthase and estrogen receptor alpha (ER-α) were assessed by Western blotting. Histological slices of coronary arteries were stained with hematoxylin and eosin, and morphometric parameters were analyzed. Oxidative stress was assessed in situ by dihydroethidium fluorescence. Ovariectomy enhanced systolic blood pressure, which was prevented only by the DRSP treatment. OVX causes endothelial dysfunction, an effect prevented by both treatments; however, the vasodilator response in the DRSP group was significantly higher at the three highest concentrations compared to the OVX group. ER-α expression decreased in OVX rats restored by the treatments. Morphometric parameters and oxidative stress were augmented by OVX and reduced by both the E2 and DRSP treatments. Hormonal therapy with E2 and DRSP may be an important therapeutic option in the prevention of coronary heart disease in the hypertensive post-menopausal women.